A qualitative exploration of dietitians' experiences of prescribing oral nutritional supplements to patients with malnutrition: A focus on shared tailoring and behaviour change support. Issue 5 (15th February 2021) - Liljeberg, Evelina; Nydahl, Margaretha; Lövestam, Elin; Andersson, Agneta
Abstract: Background: Oral nutritional supplements (ONS) are commonly prescribed to patients with malnutrition. Dietitians have been suggested as preferred prescribers but generally lack ONS prescribing rights. How dietitians with prescribing rights experience their professional practice of prescribing ONS remains understudied. Thus, by exploring dietitians' experiences of prescribing ONS, the present study aimed to obtain a deeper understanding of specific aspects that are of importance for dietitians when providing a nutrition therapy including ONS. Methods: Qualitative individual interviews were conducted with 13 dietitians prescribing ONS to free‐living adult outpatients with malnutrition or at nutritional risk in the hospital or primary care setting. Systematic text condensation was used for data analysis. Results: Two main categories signifying important aspects were identified and labelled: 'Shared tailoring of the ONS prescription' and 'Supporting and facilitating ONS use'. First, the dietitians described tailoring the ONS prescription together with the patient, having their acceptance as a prerequisite, and being flexible regarding products and amounts prescribed. Second, they described performing different communication strategies and organising of practical issues (e.g., ONS delivery and support from others) to support and facilitate patients' ONS usage. Conclusions: The present study identifies patient involvement and the role of dietitians as behaviour change facilitators as two important aspects when dietitians prescribe ONS. These findings allow for dietitians' ideals and strategies on how to prescribe ONS to be made more visible, which can inform both clinical practice and clinical trials for future improvements in nutrition therapy to address malnutrition. Abstract : When interviewing dietitians about their experiences of prescribing oral nutritional supplements (ONS) to patients with malnutrition, we identified two aspects of importance. First, the dietitians described a shared tailoring process when having patients' acceptance as a prerequisite and performing the prescription together with the patient. Second, they described performing different communication strategies and organising of practical issues to support ONS usage.